Infection sites of Sclerotium cepivorum on onion roots - McLean, K.L.; Stewart, A. (New Zealand Plant Protection, 2000)
Onion (Allium cepa) root infection by Sclerotium cepivorum was examined in two glasshouse bioassays In the first bioassay the effect of sclerotial depth was examined Sclerotia placed at 1 10 and 20 cm depths in soil filled planter bags germinated and infected onion roots at 5 7 and 13 weeks after planting respectively The second bioassay determined that the severity of infection varied when sclerotia were placed at the stem base along the length of a root and at the root tip After 22 weeks a greater (P